2008
DOI: 10.1021/jp7107279
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis and Fabrication of Semiconducting Nanorod/Nanowire Bundles of Fe[TCNQ]2(H2O)2via Electrochemically Induced Solid−Solid Phase Transformation of TCNQ Microcrystals

Abstract: A generic electrochemical approach has been employed to synthesize, fabricate, and characterize 2-D/3-D nanorod/nanowire bundles of semiconducting/magnetic Fe[TCNQ]2(H2O)2 material. The redox-based TCNQ/Fe[TCNQ]2(H2O)2 solid−solid phase transformation utilizes the one-electron reduction of TCNQ-modified electrodes coupled with ingress of Fe2+ (aq) ions, from bulk solution, into the reduced TCNQ crystal lattice via a nucleation−growth process. The reverse oxidation process, involving Fe[TCNQ]2(H2O)2/TCNQ transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…When TCNQ crystals are adhered to graphite electrodes the electroreduction provides the radical anion that is irreversibly trapped by metal ions that diffuse from the aqueous electrolyte. Thus, semiconducting salts CuTCNQ [102] and Fe(TCNQ) 2 (H 2 O) 2 were synthesized by phase changing solid-to-solid interconversions [103]. The copper salt crystals are needle shaped and the hydrated iron salt occurs as nanorod/nanowire bundles by a nucleation-growth process.…”
Section: Scheme 11mentioning
confidence: 99%
“…When TCNQ crystals are adhered to graphite electrodes the electroreduction provides the radical anion that is irreversibly trapped by metal ions that diffuse from the aqueous electrolyte. Thus, semiconducting salts CuTCNQ [102] and Fe(TCNQ) 2 (H 2 O) 2 were synthesized by phase changing solid-to-solid interconversions [103]. The copper salt crystals are needle shaped and the hydrated iron salt occurs as nanorod/nanowire bundles by a nucleation-growth process.…”
Section: Scheme 11mentioning
confidence: 99%
“…Dunbar, Miller and their co-workers reported a series of M[TCNQ] 2 -based materials with significant magnetic properties [26][27][28][29]. Bond and co-workers investigated the electrochemical syntheses of these materials [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with the magnetic properties of TCNQ-based lanthanide complexes, their electrochemical properties are hardly known. In view of the importance of electrochemical syntheses for a series of TCNQ-based transition metal materials [30][31][32]36,37], we carry out the systematic investigation of electrochemical properties on the series of TCNQ-based lanthanide complexes 1À3 and IÀVI.…”
Section: Introductionmentioning
confidence: 99%
“…
AbstractSupported bilayer lipid membrane (s-BLM) containing one-dimensional compound 1, TCNQ-based (TCNQ ¼ 7,7,8, organometallic compound {(Cu 2 (m-Cl)(m-dppm) 2 )(m 2 -TCNQ)} 1 , was prepared and characterized on the self-assembled monolayer (SAM) of 1-octadecylmercaptan (C 18 H 37 SH) deposited onto Au electrode. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) results showed that the compound 1, dotted inside s-BLM, can act as mediator for electron transfer across the membrane.
…”
mentioning
confidence: 99%
“…s-BLM has attracted extensive interest in recent years [5] and TCNQ as modifiers to mediate the electron transport through the s-BLM [6] has been found. Recently, electrochemical method in controlling the synthesis, morphology, and fabrication of TCNQ-based organometallic compounds has been employed [7]. However, the electrochemical property of TCNQ-based organometallic compounds inside s-BLM remains unknown.…”
mentioning
confidence: 99%